Analisis Implementasi dan Tantangan Subsidi Pemerintah dalam Menanggulangi Kemiskinan di Kota Tanjungpinang - Nurullaeli Uswatun Hasanah; Suci Ananda sitompul; Lestari Sitorus; Wahjoe Pangestoeti (International Forum of Researchers and Lecturers, 2025)
Poverty remains a major problem in Tanjungpinang, Riau Islands Province. The government continues to attempt to address it by providing various forms of subsidies such as BPNT, BLT, and PKH. This study aims to assess the implementation of the subsidy program and identify the problems that arise. Using a qualitative method through desk research, this study found that subsidies have a positive impact on consumption and provide temporary economic support. However, their effectiveness is hindered by inaccurate recipient data, poor coordination between agencies, budget constraints, and low digital capabilities. In addition, the sectoral approach creates overlaps between programs. Therefore, digital data integration, improved monitoring, and community empowerment are needed to strengthen long-term impact. This study recommends improvements to subsidy policies to support sustainable poverty alleviation efforts in Tanjungpinang.